Art & Language : Blurrings Works on paper 1965 - 2008. - Silverman van Coenegrachts, Jill; Harrison, Charles; Rose, Barbara; Galerie Thaddaeus Ropac, Paris (Paris/Salzburg : Galerie Thaddaeus Ropac, 2008)
Baldwin, Michael ; Ramsden, Mel
Art & Language Blurrings Works on paper 1965 - 2008, Galerie Thaddaeus Ropac, Paris, September - October 2008
kunstcatalogus